Disseminated Coccidioidomycosis Presenting as Polyarticular Septic Arthritis: A Case Report. (November 2020) - Nasrawi, Faisal; Heidari, Arash; Aljashamy, Thulfiqar; Mangat, Nishan; Bhaika, Jasbir; Kaur, Simmer; Kuran, Rasha; Johnson, Royce
Coccidioidomycosis a fungal infection endemic to southwestern United States. It is caused by inhalation of spores of Coccidioides immitis . Sixty percent of infections are asymptomatic; the remaining 40% are primarily pulmonary disease. In <1% of infections, dissemination can occur. Dissemination usually affects those with impaired cellular immunity and pregnant women, and can involve bones, joints, meninges, and skin. We present the case of a 29-year-old Hispanic male who presented to the emergency department (ED) complaining of pain and swelling of right wrist and ankle as well as left knee for 2 months. He was referred to rheumatology clinic but returned to the ED as he developed spontaneous purulent drainage from his wrist. In the ED, an arthrocentesis of 2 of the joints showed total nucleated cells of 520 000/cm 2 and 90 000/cm 2 with 61% and 93% neutrophils, respectively. Fungal culture eventually grew Coccidioides immitis from his wrist and knee. Coccidioidomycosis complement fixation titer came back >1:512. Bone scan showed uptake of adjacent bones in the affected joints. Superimposed bacterial infection of the wrist complicated the treatment course and delayed the start of liposomal amphotericin B. Eventually patient received 12 weeks of intravenous liposomal amphotericin-B with slow clinical improvement and then switched to oral isavuconazonium for maintenance therapy. This case shows that although disseminated polyarthritis coccidioidomycosis is very rare, clinicians should keep the diagnosis of disseminated synovial coccidioidomycosis in mind in patients with risk factors.